(untitled) (Quaderni di Gargnano, 2018)
This essay examines the first collections of letters written in the Italian vernacular of the 13th and 14th centuries and explores the events and circumstances that gave birth to the epistolary genre. Common to all the epistles – from Guittone’s to Santa Caterina’s – is their Tuscan origins and, even more importantly, their Christian apologetics and deliberate suppression of specific references so as to raise the level of discourse to that of a moral treatise.